Patterns in Kindergarten: Teachers' Knowledge of Content and Students and Associated Self-Efficacy Beliefs - Schreiber, Iris (Scientia in educatione, 2020)
The present study engages in sixty kindergarten teachers' knowledge and self-efficacy related to patterns. Two aspects are examined: Teachers' pedagogical knowledge of content and students (specifically, what is easy or difficult for the children and what their typical errors are) as well as teachers' self-efficacy in their knowledge. These aspects are explored about two types of patterns - a repeating pattern and a growing pattern. The results pertaining to the repeating pattern show that teachers have knowledge of children's typical errors. However, they have partial knowledge of what is easy or difficult for the children: they tend to underestimate children's performance. Regarding the growing pattern, teachers have partial knowledge of both children's typical errors and of what is easy or difficult for them: they tend to overestimate children's performance. The results may have implications for teachers' education and guidance, especially novice teachers.